(untitled) (Revista Direitos Humanos e Democracia, 2021)
This article aims to approach the crisis of liberal democracy with the rise of populist movements and their risk for democracy, from the perspective of the inter-american system. For this purpose, we analyzed three judgments of the Inter-American Court of Human Rights, identifying two important aspects: the populist tendency to attack judicial independence and the principle of separation of powers; and the essentiality of joint action by internal and international institutional actors in the protection of basic democratic principles, considering the impact of the Inter-American System of Human Rights.